2010
DOI: 10.1210/en.2010-0426
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Increases Systemic and Local Uterine Proportions of CD4+CD25+ Treg Cells during Midterm Pregnancy in Mice

Abstract: Mechanisms maintaining the growth of a "semi-foreign" fetus within the maternal uterus via immune tolerance remain unclear. CD4(+)CD25(+) regulatory T (Treg) cells have been implicated in the maintenance of maternal-fetal immune tolerance. Additionally, 17β-estradiol (E2) is able to initiate immune suppression through CD4(+)CD25(+) Treg cells during early pregnancy. Little is known, however, regarding the relationship between progesterone (P4) and immune tolerance during midterm pregnancy, an important period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 41 publications
8
117
2
3
Order By: Relevance
“…5 The withdrawal of hormones at the end of pregnancy may affect FoxP3 expression by Treg cells, which was shown to be enhanced by progesterone in human studies. 3 Other authors postulate that progesterone, whose maximum levels are seen at the end of pregnancy, has the capacity to reduce FoxP3 expression by Treg cells in vitro. 25 Moreover, recent data indicate a significant decrease of Treg cells expressing FoxP3 in the 3rd trimester and women in labour at term.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The withdrawal of hormones at the end of pregnancy may affect FoxP3 expression by Treg cells, which was shown to be enhanced by progesterone in human studies. 3 Other authors postulate that progesterone, whose maximum levels are seen at the end of pregnancy, has the capacity to reduce FoxP3 expression by Treg cells in vitro. 25 Moreover, recent data indicate a significant decrease of Treg cells expressing FoxP3 in the 3rd trimester and women in labour at term.…”
Section: Main Findingsmentioning
confidence: 99%
“…2 The abundance or modulation of systemic regulatory T cells (Treg) could be involved in pregnancy complications. 3,4 However, it is not known whether the Treg suppressive mechanism is specific to PTB or if it is also involved in spontaneous normal term birth. 5 Progesterone has a major role in pregnancy maintenance and its secretion has been demonstrated in the amnion, chorion and decidua in humans.…”
Section: Introductionmentioning
confidence: 99%
“…stasis by inhibiting overshooting reactions in a number of tissues in the body (31)(32)(33). Both progesterone and HMOX-1 can suppress CD4 + effector T cell responses and induce the generation of CD4 + Tregs (34)(35)(36)(37), which also promote maternal immune tolerance to the fetus (38,39). Maternal CD8 + T cell responses can also affect placental function (40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, physiological doses of progesterone were shown to significantly increase the population of Treg cells (Lee et al, 2011;Mao et al, 2010). However, in contrast to these data, Mjosberg et al showed using an in vitro model, that progesterone reduced the Treg cell population in PBMC from nonpregnant women (Mjosberg et al, 2009).…”
Section: Progesteronementioning
confidence: 92%